Enhanced gingival recession coverage by Er,Cr:YSGG laser root biomodification - Thamaraiselvan Murugan; Dipika Inbasekaran; Karthikeyan Murthykumar (Wolters Kluwer Medknow Publications, 2021)
Gingival recession predisposes to functional and aesthetic concerns, for which many surgical procedures are available. Among these, till now subepithelial connective graft is considered as the gold standard technique for its higher predictability of achieving recession coverage. However, it does not heal by new attachment, thus many techniques to promote new attachment such as root biomodification are done. This case enumerates the use of Er, Cr: YSGG laser for root biomodification to treat a wide and deep gingival recession defect by subpedicle connective tissue graft. Six months results show better recession coverage inspite of a wide and deeper defect. Thus, Er, Cr: YSGG laser can be an adjunctive tool to enhance the recession coverage.